1982
DOI: 10.2134/agronj1982.00021962007400030017x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Accumulations of Cadmium and Zinc by Corn Hybrids Grown on Soil Amended with Sewage Sludge1

Abstract: Researchers have recognized that different varieties and cultivars of plants subjected to the same growing conditions frequently take up different amounts of essential and nonessential trace elements. Differences in uptake appear to be predisposed genetically. In designing studies to determine the nature of the inherited capacity of corn (Zea mays L.) to control the uptake of heavy metals some additional information was needed. The objectives of this study were to determine the extent to which Cd uptake was af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Thus, the different shoot Cd concentrations in the inbreds are neither related to the growth stage of the plant, nor to the growing substrate, pH or level of Cd supply. This supports the notion of a genetic background, as was concluded by Hinesly et al (1982) and . This independence from external factors and their low Cd amounts in the shoots makes the 'shoot Cd excluders' attractive for plant breeders considering the desirable reduction of the Cd load of the food chain.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the different shoot Cd concentrations in the inbreds are neither related to the growth stage of the plant, nor to the growing substrate, pH or level of Cd supply. This supports the notion of a genetic background, as was concluded by Hinesly et al (1982) and . This independence from external factors and their low Cd amounts in the shoots makes the 'shoot Cd excluders' attractive for plant breeders considering the desirable reduction of the Cd load of the food chain.…”
Section: Resultssupporting
confidence: 89%
“…Maize inbred lines exposed to various Cd levels in the soil showed huge differences in the Cd concentrations in the shoots (Hinesly et al, 1978). These differences are believed to be genetically controlled (Hinesly et al, 1982). In previous work we have shown that in maize inbred lines internal distribution rather than total uptake causes the variation in the shoot Cd concentration .…”
Section: Introductionmentioning
confidence: 91%
“…Differences in zinc concentration among isolines were significant at only Langdon (P < 0.05) in 1995 (Table 3), and marginally so at Regina (P < 0.10), suggesting that Cd and Zn accumulation is controlled by independent mechanisms. Hinesly et al (1982) found that grain zinc concentration was not significantly different between low and high cadmiumaccumulating maize hybrids, although leaf zinc concentration was greater for the high accumulator in 2 of 3 yr. They also concluded that cadmium and zinc accumulation are genetically independent traits.…”
Section: Resultsmentioning
confidence: 78%
“…To breed crop cultivars with low Cd accumulation, it is important to find out genotypic difference in potential of Cd tolerance/accumulation in existing varieties/lines and their physiological responses to Cd addition. The uptake/tolerance of Cd varies among plant species, and also within a species, for example, soybean [12], maize [13], and lettuce [14]. Our previous study demonstrated the significant genotypic differences in Cd absorption and biomass production response to Cd stress in 11 barley genotypes [15], indicating the possibility to select varieties with low accumulation and highly tolerant to Cd.…”
mentioning
confidence: 97%